2009
DOI: 10.1088/1742-5468/2009/10/l10001
|View full text |Cite
|
Sign up to set email alerts
|

Exact and limit distributions of the largest fitness on correlated fitness landscapes

Abstract: We study the distribution of the maximum of a set of random fitnesses with fixed number of mutations in a model of biological evolution. The fitness variables are not independent and the correlations can be varied via a parameter ℓ = 1, ..., L. We present analytical calculations for the following three solvable cases: (i) one-step mutants with arbitrary ℓ (ii) weakly correlated fitnesses with ℓ = L/2 (iii) strongly correlated fitnesses with ℓ = 2. In all these cases, we find that the limit distribution for the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…It should be noted that the extreme value distribution of correlated fitnesses may change from the corresponding i.i.d. class even if correlations are weak (Jain et al, 2009;Jain, 2011). In the following discussion, we assume that the sequence fitnesses are uncorrelated and deal with the correlated fitnesses in the last subsection of this section.…”
Section: Models and Methodsmentioning
confidence: 99%
“…It should be noted that the extreme value distribution of correlated fitnesses may change from the corresponding i.i.d. class even if correlations are weak (Jain et al, 2009;Jain, 2011). In the following discussion, we assume that the sequence fitnesses are uncorrelated and deal with the correlated fitnesses in the last subsection of this section.…”
Section: Models and Methodsmentioning
confidence: 99%
“…2a for two values of r shifts towards right with increasing r as the average w E = 1 + (55r/36) [29]. Figure 2b shows that the extreme value distribution at fixed r peaks at larger w as δ increases.…”
Section: A Distribution Of the Largest Fitness At Constant Hamming Dmentioning
confidence: 89%
“…II, the largest fitness at a constant Hamming distance from the initial sequence only need to be considered for this purpose. This led us to consider the problem of the extreme statistics of correlated random variables [20,29] which has been much less studied than its uncorrelated counterpart. We found that the extreme value distribution is not of the Gumbel form which is obtained when the random variables are i.i.d.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this article, we focus on the extreme value distribution for nonindependent and identically distributed (ni.i.d.) random variables (for some results on nonindependent and nonidentically distributed fitnesses, see [6,23]). Such ni.i.d.…”
Section: Distribution Of the Largest Fitnessmentioning
confidence: 99%